Investigation of flow patterns and measurement of actual bubble velocity using void fraction profile in a vertical industrial scale two-phase flow channel / Nur Adania Nor Azman - Nur Adania, Nor Azman (2022)
Measurement of void fraction for two-phase flows involving gas and liquid in a vertical channel have been extensively researched to improve cooling system designs for energy-related industries and process refineries. Void fraction is the representation of gas and liquid ratio in a flow channel at certain working conditions. Using the Constant Electric Current Method (CECM), void fractions were obtained using sensor electrodes connected to data acquisition (DAQ) hardware which outputs the results to LabVIEW® software. Three sets of experiment were run at three fixed liquid superficial velocities,